Ultrasound Imaging and Ovarian Follicles Growth of Mares at Nirwana Equestrian Club - Indana, Khoiru; Eryka Apriyani; Ayuastari, Lisa; Hanani, Anhar Faisal (CV. Komunitas Dunia Peternakan, 2024)
Mares in the estrus cycle by the form of reproductive determine the precision of ovulating time so that efficient to the appropriate time of artificial insemination for breeding. The determination requires supporting medical equipment such as Ultrasonography during the ovulation. This research was conducted to know the ovarian follicle imaging of mares during estrus with Ultrasonography that helps through presume ovulation and the appropriate time to proceed with artificial insemination. This observation was conducted at Nirwana Equestrian Club Semarang, from October until December 2023. The sampling is collected by purposive sampling method where the sample is specifically the mares while in their estrus symptom. The collected data and information are processed descriptively using laboratory equipment such as Ultrasonography. The observation collected the mares physical estrus symptoms such as urination, vulvar pulsination, and vaginal fluid discharge. Significant development was observed from the initial follicle size of 5.34 cm to 5.61 cm in one of the samples with the examination interval within 18 hours before the occurrence of the corpus luteum. The results were proved by 9 samples of mares that had been measured with ultrasound during their estrus, and undergoing pregnancy by one attempt of artificial insemination. The optimum time for artificial insemination for mare is during ovulation where the effective precision is supported by ultrasonography.